PENGARUH BRAND IMAGE , GAYA HIDUP, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN CAFÉ TIGA TJERET DI SURAKARTA - Rendika Putri Kartika; Ida Aryati; Rochmi Widayanti (ITB AAS INDONESIA Surakarta, 2019)
The purpose of this research aims to find out and explain the simultaneous and partial influence of brand image, lifestyle, and location on the purchasing decisions of the three tjeret café in Surakarta. This research uses descriptive quantitative research design. The population of all visitors to café Tiga Tjeret and having samples using the Sugiyono formula is 100 respondents. The sampling technique uses incidental sampling, a questionnaire used for data collection of multiple linear regression analysis. The results of this study indicate that the test f brand image, lifestyle and location simultaneously and significantly influence the purchasing decision of the café three tjeret in Surakarta. The results of the t test show that the brand image, lifestyle and location have a positive and significant effect on the purchasing decisions of the three tjeret café in Surakarta. The results of the coefficient of determination (R2) show that brand image, lifestyle and location have an effect of 60.9% on the purchasing decisions of the three teretas café in Surakarta. The dominant influence in café three tjeret purchasing decisions is that lifestyle variables have a t count of 10, 423. Keywords: Brand image, Lifestyle, Location, Purchase decision.